Translated memories: Shared teaching in teacher training - Gilberto Ferreira Silva; Maria Rosa Fontebasso (Arizona State University, 2013)
The authors explore analytically their memories of shared experience of teaching during the initial training class for beginner teachers. Contexts to recover from fragments of what selective memory allows revitalized. Reflections are woven into what dimensions as the strangeness, power, insecurity and personal beliefs are being gradually revealed, worked, giving way to partnership, complicity and reaffirmation of commitment to education. This work highlights the contributions that the use of memory offers reflective processes to make education but triggered later times. Thus discloses an alternative to more analytical processes to trigger on what we do in education, especially in the field of teacher education.